Level of Learning Independence in Elementary School Students: The Influence of Self-Efficacy, Motivation, and Peer Interaction - Arfan Triwiratman; Toto Nusantara; Imanuel Hitipeuw (South Sulawesi Education Development (SSED), 2023)
This study aims to analyze the influence of self-efficacy, learning motivation, and peers on student learning independence in elementary schools. The research method used was a survey and data analysis using regression techniques. The research sample consisted of fourth-grade students in two elementary schools, totaling 65 people. Data were collected through questionnaires that measured the level of self-efficacy, learning motivation, peers, and learning independence. The results showed that self-efficacy is positively and significantly related to the level of students' learning independence. The higher the level of students' self-efficacy, the higher the level of learning independence they show. In addition, learning motivation also has a positive influence on learning independence. Students who have high learning motivation tend to be more independent in overcoming their learning challenges. In addition to self-efficacy and learning motivation, peers also play an important role in students' learning independence. The results showed that supportive and positive peer relationships were associated with higher levels of learning independence. Based on these findings, efforts to improve students' learning independence can focus on strengthening self-efficacy and learning motivation, as well as creating an environment that supports positive relationships with peers.